Descriptions of larval flatfishes of the genera psettodes (Psettodidae) andpseudorhombus (paralichthyidae)from the great barrier reef, Australia - Liew, Hock-Chark; Milward, Norman E.; Hartwick, Robert F. (CSIRO Publishing, 1988)
The larval developmental stages of five of the eight species of Psettodes and Pseudorhombus known from the shelf waters of the central Great Barrier Reef are described and illustrated. The species treated include Psettodes erumei (3 -3-13 -0 mm body length, BL), Pseudorhombus arsius (2-9-11 -5 mm BL), P. elevatus (3-4-10-0 mm BL), P. diptospilus (4-2-12-6 mm BL) and P. spinosus (2-5-12-7 mm BL). Meristic characters were reliable for identifying larvae only if full complements of these characters had been acquired. Smaller larvae were identified on the basis of pigmentation and head spination or spinulation patterns. The settling sizes of these larvae were estimated based on the stage of eye migration.